2006
DOI: 10.1111/j.1365-2249.2006.03051.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin (IL-10) in probiotic-mediated immune modulation: an assessment in wild-type and IL-10 knock-out mice

Abstract: While the impact of Bifidobacterium infantis 35624 and other probiotics on cytokines has been shown in established colitis, the effects of B. infantis consumption in pre-inflammation of interleukin (IL)-10 knock-out (KO) mice and on the wild-type (WT) C57Bl/6 mice have not been well demonstrated. The objective of this study was to examine cytokine responses in mucosal and systemic lymphoid compartments of IL-10 KO mice early in disease and to compare with control WT mice. Mice were fed B. infantis or placebo f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 49 publications
1
38
2
6
Order By: Relevance
“…Beneficial effect of probiotics was tested to treat IBD. L. plantarum or B. infantis were able to decrease the level of INF-g in IL-10 knock out (KO) mice that spontaneously develop colitis (13,14). We also demonstrated that administration of L. casei or IRT5 probiotics could prevent or suppress diverse immune diseases (15,16).…”
Section: The Role Of Probiotics In Immune Disordersmentioning
confidence: 80%
See 1 more Smart Citation
“…Beneficial effect of probiotics was tested to treat IBD. L. plantarum or B. infantis were able to decrease the level of INF-g in IL-10 knock out (KO) mice that spontaneously develop colitis (13,14). We also demonstrated that administration of L. casei or IRT5 probiotics could prevent or suppress diverse immune diseases (15,16).…”
Section: The Role Of Probiotics In Immune Disordersmentioning
confidence: 80%
“…Maintenance of immune balance between the effector and regulatory T cell (Treg) is crucial to suppress development and progression of immune disorders (14,19). Especially, maintenance of immune homeostasis is really critical at the mucosal sites where large amounts of antigens always encounter with host immune system.…”
Section: Foxp3mentioning
confidence: 99%
“…Further studies examined the effect of Bfdbm infantis 35624 on early inflammation in IL-10 -/-mice and wildtype mice of the same genetic background. Pronounced changes occurred in the Peyer's patch following probiotic consumption, with IFN-reduced in both wild-type and IL-10 -/-mice [62].…”
Section: Iva-probiotic Effect In Animal Experimental Ibd Modelsmentioning
confidence: 99%
“…5,19,20) This method is, however, not suitable for the screening of hundreds of LAB strains at once and consumes an excessive number of laboratory animals. Therefore, a system in which PP-cells are co-cultured with LAB may be a convenient and useful tool for estimating the influence of LAB on intestinal immunity.…”
Section: -18)mentioning
confidence: 99%
“…[15][16][17][18] The effect of probiotics on intestinal immunity has been investigated using laboratory animals; IgA assessments were conducted using isolated intestine, feces, or a culture of ex vivo Peyer's patch cells (PP-cells) after oral administration of LAB. 5,19,20) This method is, however, not suitable for the screening of hundreds of LAB strains at once and consumes an excessive number of laboratory animals. Therefore, a system in which PP-cells are co-cultured with LAB may be a convenient and useful tool for estimating the influence of LAB on intestinal immunity.…”
mentioning
confidence: 99%